Innovative China Innovation Race Between East and West - van Someren, Taco C.R. (Management for Professionals,, 2013)
China is trying to turn its labor, capital and resources intensive, lower added-value and export dependent growth into a sustainable innovative economy. This is changing the world’s power balance and has sparked a race between East and West in knowledge-based, high added-value economic innovation. Inspired by their extensive experience in doing business with China, the authors show how the US, the EU and China have reached a crossroad where ten battle fields decide about their future earning capacity and prosperity. Whether China will be a threat or an opportunity depends on the main players in government, public and private organizations rethinking their innovation policies and paths of business development. This books offers a new view on innovation which can be applied by corporate leaders and policy makers to get ready for the future.